A method of preparing a self-supporting graphite film and a soft x-ray detector

CN118239483BActive Publication Date: 2026-10-27YANGTZE RIVER DELTA PHYSICS RES CENT CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410407489.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-07
Publication Date
2026-10-27
Estimated Expiration
2044-04-07

AI Technical Summary

Technical Problem

但是,常规的X射线水窗探测器是基于纯半导体材料,无狄拉克锥能带结构,热电子增益效应较差;且体相二维半导体材料尚不能大面积制备

Benefits of technology

[0022](1)溶剂在离心力作用下形成周向的剪切,对氧化石墨烯进行取向和大面积、尺寸可控的制备,且取向结构的达成会提升聚合物自身的石墨化能力,降低氧化石墨烯的用量;均匀取向的结构使得所制备薄膜在后续相分离过程中可以保持均匀的应力和结构的完整。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118239483B_ABST
    Figure CN118239483B_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing a self-supporting graphite film and a soft X-ray detector, and the method for preparing the self-supporting graphite film utilizes a centrifugal filtration technology to prepare a composite film with controllable size, orientation and humidity; utilizes a controllable phase separation technology to realize rapid separation of the composite film and a substrate; utilizes efficient volatilization of a solvent and high roughness of the substrate to realize self-supporting of the film; and utilizes high-temperature annealing to repair a material lattice structure. The graphite film prepared by the technical scheme is controllable in three-dimensional size, high in preparation efficiency, simple in operation scheme, recyclable in reagent, and low in energy consumption, and can be used for industrialized and batch preparation of multifunctional nanometer films. The self-supporting graphite nanometer film is heterogeneously integrated with a semiconductor material, a thick graphite film is used to realize high multiplication of photoelectric signals under soft X-rays, and low-dose and high-sensitivity detection in the water window X-ray field is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of graphene film preparation, and relates to a method for preparing a self-supporting graphene film and a soft X-ray detector. Background Technology

[0002] The rapid development of two-dimensional materials, such as graphene, has brought new opportunities for breakthroughs in the performance and functional expansion of traditional functional thin films. In particular, graphite films combine the high thermal conductivity, high electrical conductivity, and long carrier lifetime of monolayer graphene with the thick cross-section of particles and matter in bulk materials, thus enabling their wide application in thermoacoustic devices, electromagnetic shielding, broadband detection, molecular sensing, and bioelectrodes. However, due to limitations in preparation methods, large-area fabrication of nano-thickness, uniformity, controllable size, and high crystallinity graphite films has not yet been achieved.

[0003] Common methods for preparing graphite films include vacuum filtration, blade coating, and spinning. However, these methods cannot achieve high orientation of the film or rapid detachment from the substrate, thus they are unsuitable for industrial production. Specifically, vacuum filtration has extremely low efficiency, poor controllability of lateral dimensions, and uncontrollable film orientation, making it only suitable for laboratory preparation. Blade coating can prepare nanofilms over large areas, but substrate detachment is difficult, time-consuming, and prone to damage, and material orientation control is poor, making it unsuitable for industrial production. Centrifugal filtration can solve the problems of large-area preparation, uniformity, and material orientation of nanofilms, but the prepared nanofilms cannot detach well from the substrate, and its heating and evaporation drying is extremely energy-intensive, with the evaporated solvent difficult to recover, resulting in high industrial production costs.

[0004] Nanoscale-thick, highly crystalline graphite nanofilms better reflect the bulk characteristics of graphene, such as in low-dose, high-sensitivity X-ray detectors. In the water window band (i.e., the wavelength range of soft X-rays between 2.34 nm and 4.4 nm), water does not absorb X-rays, making it transparent to X-rays in this band. However, soft X-rays in this range can be absorbed by other elements constituting biological organisms (carbon, nitrogen, etc.), thus enabling the detection and imaging of live biological cell samples. However, conventional X-ray water window detectors are based on pure semiconductor materials, lacking Dirac cone band structures and exhibiting poor hot electron gain effects; furthermore, bulk two-dimensional semiconductor materials cannot yet be fabricated on a large scale. Summary of the Invention

[0005] This invention addresses the shortcomings of existing technologies by providing a method for preparing self-supporting graphite films. It utilizes the circumferential shearing effect of a solvent during centrifugation to orient the two-dimensional material, thus preparing a composite film with controllable size, orientation, and humidity. Furthermore, it employs controlled phase separation technology to achieve rapid separation of the composite film from the substrate. This method overcomes the technical barriers of ultrathin film orientation and size control, as well as rapid separation from the substrate, enabling controllable preparation of graphite films and their wide application in numerous fields.

[0006] This invention also provides a soft X-ray detector. After the ultrathin film is fabricated, it can be integrated with a semiconductor substrate to obtain a high-performance optoelectronic heterojunction. The significant feature of the semiconductor substrate in the water window band is its high photon absorption efficiency in the soft X-ray region. Based on this, high orientation leads to low electron-phonon scattering and long hot electron lifetime. The high absorption of the self-supporting graphite nanofilm results in high hot electron concentration and low electron-phonon scattering characteristics, which contribute to high hot electron gain capability, thus facilitating sensitive X-ray detection in the water window band. By utilizing the strong absorption of soft X-rays by the semiconductor and the enhanced electron-electron interaction of the graphite structure of the ultrathin bulk graphite nanofilm, low-dose, high-sensitivity detection and imaging can be achieved.

[0007] Specifically, the present invention adopts the following technical solution:

[0008] A method for preparing a self-supporting graphite film includes the following steps:

[0009] (1) The dispersion of graphene oxide is injected into a rotating centrifuge tube at one time, and an incompletely dried graphene oxide film is formed on the inner wall of the centrifuge tube. The solvent volume content is 10-40%. The centrifuge tube is made of filter membrane and is arranged along the horizontal axis.

[0010] (2) Immerse the filter membrane carrying the incompletely dried graphene oxide membrane in a highly volatile solvent to separate the graphene oxide membrane from the filter membrane.

[0011] (3) Remove the graphene oxide film from the highly volatile solvent using a carrier. After drying, the graphene oxide film separates from the carrier to obtain the graphene oxide film. Generally, polytetrafluoroethylene with an average roughness higher than 2 μm is used. The high roughness of polytetrafluoroethylene will greatly reduce the promotion of solvent evaporation, reduce the contact area and interfacial energy between the film and the substrate, and thus quickly separate from the substrate after subsequent drying.

[0012] (4) The graphene oxide film is placed in air at 200-300℃ for 0.5-2 hours, and then treated in a graphite furnace at 2500℃ or above for more than 2 hours under argon protection to obtain a self-supporting graphene film. The thickness of the sintered self-supporting graphene film is about half that of the graphene oxide-polymer composite film.

[0013] The solvent for the dispersion of graphene oxide in step (1) can be any solvent used in the prior art for dispersing graphene oxide, including but not limited to water.

[0014] Furthermore, the rotation speed is 500 r / min or higher, including but not limited to 500–12000 r / min, and the inner diameter of the centrifuge tube is 20–100 cm. During centrifugation, on the one hand, the two-dimensional material adheres to the filter membrane under the action of centrifugal force; on the other hand, the solvent forms circumferential shear under the action of centrifugal force, orienting the two-dimensional material. The higher the rotation speed and / or the larger the diameter, the stronger the shear force of the solvent.

[0015] Furthermore, the graphene oxide dispersion is formed by dissolving graphene oxide in a solvent and a graphitizable polymer, wherein the graphitizable polymer and graphene oxide account for 0.05 wt% to 1 wt% of the dispersion; and the mass ratio of the graphitizable polymer to graphene oxide is 10:10 to 1:10.

[0016] Furthermore, the graphitizable polymer can be polyacrylonitrile, lignin, or polyimide, or other graphitizable and dispersible polymers.

[0017] Furthermore, the solvent is dimethylformamide, dimethylacetamide, or N-methylpyrrolidone.

[0018] Furthermore, the filter membrane is a hydrophilic polytetrafluoroethylene filter membrane.

[0019] Furthermore, the highly volatile solvents in step (3) include, but are not limited to, highly volatile solvents such as isopropanol, ethanol, acetone, and ethyl acetate.

[0020] A soft X-ray detector, comprising a semiconductor substrate and a self-supporting graphite film prepared by the above method, the two being heterogeneously integrated; the semiconductor substrate has a thickness of 2nm to 20nm and serves as the main X-ray photon absorbing layer; the self-supporting graphite nanofilm has a thickness of 5nm to 50nm and serves as the secondary absorption layer and the main gain layer; and incident X-ray photons can be simultaneously incident from either the semiconductor substrate or the graphite nanofilm layer.

[0021] The beneficial effects of this invention are as follows:

[0022] (1) The solvent forms circumferential shear under centrifugal force, which can oriented graphene oxide and prepare large-area, size-controllable graphene oxide. The achievement of the orientation structure will enhance the graphitization ability of the polymer itself and reduce the amount of graphene oxide used. The uniform orientation structure allows the prepared film to maintain uniform stress and structural integrity during the subsequent phase separation process.

[0023] (2) Under the premise that the coated film is not completely dry (the stacked structure is fixed), the solvent is used to quickly fill the interface between the composite film and the substrate by utilizing the exchange between the highly volatile solvent and the film-forming solvent and the phase separation and solidification effect on the composite film, so as to achieve rapid separation between the composite film and the substrate.

[0024] (3) By utilizing the high roughness and high porosity of the polytetrafluoroethylene (PTFE) film, the interfacial bonding force between the film and the substrate is reduced, thereby enabling the film to quickly self-support. In summary, this technology lays the practical foundation for the industrial production of graphite films with a wide thickness range and low cost.

[0025] Based on the preparation of the aforementioned ultrathin self-supporting graphite film (nano-thickness), this invention integrates the prepared highly oriented graphite nanofilm with a semiconductor heterostructure. Utilizing the high absorption of soft X-rays in the water window band by the semiconductor substrate and the highly oriented graphite nanofilm, along with the low electron-phonon scattering and long hot electron lifetime resulting from the high orientation, low-dose, high-sensitivity detection of X-rays in the water window band can be prepared and realized. Since soft X-rays are absorbed more strongly in thin materials compared to hard X-rays, the integration of a thinner semiconductor film with the graphite nanofilm holds promise for real-time, high-resolution imaging and detection of living biological cells. Attached Figure Description

[0026] Figure 1 This is a schematic diagram of the production equipment for graphene oxide film in Example 1 of the method for preparing a self-supporting graphene film according to the present invention.

[0027] Figure 2 (a) is a schematic diagram of the principle of graphene oxide film forming and peeling. Figure 2 (b) is an enlarged diagram of the graphene oxide film forming and peeling principle;

[0028] Figure 3 This is a photograph of the graphite film prepared in Example 3;

[0029] Figure 4 This is a transmission electron microscope (TEM) image of a 50 nm graphite film cross-section prepared in Example 3;

[0030] Figure 5 XPS image of the graphite film prepared in Example 3;

[0031] Figure 6 Raman image of the graphite film prepared in Example 3;

[0032] Figure 7 The detection sensitivity diagram of the graphite nanofilm / silicon heterojunction in Example 4 under the soft X-ray band is shown.

[0033] The components include a centrifuge cylinder 1, a support cylinder 2, a flow guiding structure 3, and a driving device 4. Detailed Implementation

[0034] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with the accompanying drawings and preferred embodiments, is provided below.

[0035] Example 1

[0036] A method for preparing a self-supporting graphite film includes the following steps:

[0037] (1) Graphene oxide and polyacrylonitrile are uniformly dispersed in dimethylformamide to form a dispersion of graphene oxide. The mass ratio of polyacrylonitrile to graphene oxide is 10:1. In the dispersion of graphene oxide, the proportion of polyacrylonitrile to graphene oxide is 0.05 wt%.

[0038] (2) The dispersion of graphene oxide is injected into the rotating centrifuge tube 1 in one go, such as... Figure 1 As shown, an incompletely dried graphene oxide film is formed on the inner wall of centrifuge cylinder 1, with a solvent volume content of 10%. Centrifuge cylinder 1 is composed of a filter membrane and is arranged along a horizontal axis. In this embodiment, the horizontally arranged centrifuge cylinder 1 is supported by a rigid support cylinder 2. To achieve solvent shearing of the solute, the support cylinder 2 in this embodiment has a flow guiding structure 3 to guide the solvent filtered through the filter membrane from the outer wall of centrifuge cylinder 1. Thus, it utilizes the circumferential shearing formed by the solvent during centrifugal escape to orient the two-dimensional material. In this embodiment, the flow guiding structure 3 consists of uniformly distributed through holes on the cylinder wall of the support cylinder 2 with a pore diameter of 5 micrometers. Due to the small pore diameter, when the graphene oxide film production equipment is not turned on or at low speed, the centrifugal force is insufficient to throw the liquid out of the support cylinder 2.

[0039] (3) Immerse the filter membrane containing the incompletely dried graphene oxide membrane in a highly volatile solvent to separate the graphene oxide membrane from the filter membrane (see principle). Figure 2 (a), 2(b));

[0040] (4) The graphene oxide film was removed from the highly volatile solvent using polytetrafluoroethylene with a roughness of 2 μm. After drying, the graphene oxide film was separated from the support to obtain the graphene oxide film. The highly volatile solvent was isopropanol.

[0041] (5) The self-supporting composite membrane is placed in air at 200°C for 2 hours and then treated in a graphite furnace at 2500°C or above for more than 2 hours under argon protection to obtain a self-supporting graphite membrane.

[0042] Using the above method, a highly crystalline self-supporting graphite nanofilm was obtained with a thickness of approximately 1 μm, a length of 62.8 cm, and a graphitization degree of 98%. No heteroatoms or atomic defects were found within a 100 μm range of the exfoliated monolayer graphene structure, and its orientation degree was measured to be 98.6%.

[0043] Example 2

[0044] A method for preparing a self-supporting graphite film includes the following steps:

[0045] (1) Graphene oxide and lignin are uniformly dispersed in dimethylacetamide to form a dispersion of graphene oxide. The mass ratio of lignin to graphene oxide is 5:5. In the dispersion of graphene oxide, the proportion of lignin to graphene oxide is 0.5wt%.

[0046] (2) The dispersion of graphene oxide is injected into the rotating centrifuge tube 1 in one go, and an incompletely dried graphene oxide film is formed on the inner wall of the centrifuge tube 1. The solvent volume content is 25%. The centrifuge tube 1 is composed of a filter membrane and is arranged along the horizontal axis. The arrangement of the centrifuge tube 1 in this embodiment is the same as that in embodiment 1, except that: the inner diameter of the centrifuge tube 1 is 100 cm, the rotation speed of the centrifuge tube 1 and the support tube 2 is 1000 r / min, and the centrifugation time is 10 min.

[0047] (3) Immerse the filter membrane carrying the incompletely dried graphene oxide membrane in a highly volatile solvent to separate the graphene oxide membrane from the filter membrane.

[0048] (4) The graphene oxide film was removed from the highly volatile solvent using polytetrafluoroethylene with a roughness of 3 μm. After drying, the graphene oxide film was separated from the carrier to obtain the graphene oxide film. The highly volatile solvent was ethanol.

[0049] (5) The self-supporting composite membrane is placed in air at 250°C for 1 hour, and then treated in a graphite furnace at 2500°C or above for more than 2 hours under argon protection to obtain a self-supporting graphite membrane.

[0050] Using the above method, a highly crystalline self-supporting graphite nanofilm was obtained with a thickness of approximately 5 nm, a length of 188.4 cm, and a graphitization degree of approximately 98%. No heteroatoms or atomic defects were found within a 100 μm range of the exfoliated monolayer graphene structure, and its orientation degree was measured to be 98.3%.

[0051] Example 3

[0052] A method for preparing a self-supporting graphite film includes the following steps:

[0053] (1) Graphene oxide and polyimide are uniformly dispersed in N-methylpyrrolidone to form a dispersion of graphene oxide. The mass ratio of polyimide to graphene oxide is 1:10. In the dispersion of graphene oxide, the proportion of polyimide to graphene oxide is 1 wt%.

[0054] (2) The dispersion of graphene oxide is injected into the rotating centrifuge cylinder 1 in one go, and an incompletely dried graphene oxide film is formed on the inner wall of the centrifuge cylinder 1. The solvent volume content is 40%. The centrifuge cylinder 1 is composed of a filter membrane and is arranged along the horizontal axis. The arrangement of the centrifuge cylinder 1 in this embodiment is the same as that in embodiment 1, except that: the inner diameter of the centrifuge cylinder 1 is 20 cm, the rotation speed of the centrifuge cylinder 1 and the support cylinder 2 is 9000 r / min, and the centrifugation time is 5 min.

[0055] (3) Immerse the filter membrane carrying the incompletely dried graphene oxide membrane in a highly volatile solvent to separate the graphene oxide membrane from the filter membrane; the highly volatile solvent is acetone.

[0056] (4) The graphene oxide film was removed from the highly volatile solvent using polytetrafluoroethylene with a roughness of 5 μm. After drying, the graphene oxide film and the carrier were separated to obtain the graphene oxide film.

[0057] (5) The self-supporting composite membrane is placed in air at 300°C for 0.5 hours and then treated in a graphite furnace at 2500°C or above for more than 2 hours under argon protection to obtain a self-supporting graphite membrane.

[0058] This embodiment obtains a silvery-bright surface using the above method. Figure 3 ), thickness approximately 50nm ( Figure 4 ), free of heteroatoms Figure 5 () Defect content less than 0.003 Figure 6 The self-supporting graphite nanofilm has a length of 314 cm and a graphitization degree of about 99% (orientation degree is a parameter of the initial raw material film. After graphitization, the original orientation degree will be retained. Orientation degree determines graphitization degree. Since the graphitization degree is 99%, it means that the orientation degree is not less than 99%). No heteroatoms or atomic defects were found in the 100 μm range of the exfoliated monolayer graphene structure.

[0059] Example 4

[0060] A soft X-ray detector, using a 20nm thick, 1 -10The device was fabricated using a standard SOI wafer of n-type silicon with a top-side resistivity of (100) Ω·cm. A silicon dioxide layer approximately 100 nm thick was grown on the top-side silicon of a standard 20 nm thick lightly doped n-type silicon SOI wafer using a thermal oxidation process. The silicon window (for the ohmic contact region) was patterned using UV lithography, followed by silicon dioxide etching in buffered oxide etching (BOE). A 40 nm thick Ti electrode was fabricated in the aforementioned silicon window using sputtering and lift-off processes, followed by RTP (rapid thermal annealing) at 750 °C (20 s) and 850 °C (20 s) to form a good ohmic contact with silicon. Next, the silicon dioxide layer was again patterned using photolithography. Ti / Au (15 nm Ti, 50 nm Au) was then prepared by electron beam evaporation, and electrodes were formed using a lift-off process with acetone and IPA. Finally, the silicon window (2 mm × 2 mm) was patterned using UV lithography. The silicon dioxide in the silicon window was then etched away using BOE solution.

[0061] The 50 nm thick self-supporting graphene nanofilm prepared in Example 3 was transferred to the silicon window using distilled water and nitrogen purging, or the 5 nm thick self-supporting graphene nanofilm prepared in Example 2, or a 2 nm thick low-orientation graphene nanofilm layer. The surface tension of water facilitated the unfolding of the graphene oxide composite film and allowed it to adhere smoothly to the silicon. Water was removed from the self-supporting graphene nanofilm by high-pressure nitrogen purging, leaving a flat film with atomically conformal contact with the silicon substrate. Additional portions of the graphene oxide composite film outside the Ti / Au electrode were then etched using photolithography and ICP processes. Finally, gold wire bonding was used to connect the device and the designed logic circuitry to fabricate carbon-based soft X-ray detectors I, II, and III.

[0062] Testing the soft X-ray response sensitivity of this device I under a -1V bias voltage as a function of incident dose yields results such as... Figure 7 The results shown demonstrate a high response sensitivity, proving its applicability for the detection and assessment of living biological cells in the water window X-ray band.

[0063] To compare the sensitivity differences between graphene film / silicon heterojunction devices and other soft X-ray detectors, the following devices were fabricated:

[0064] Detector I: Employs the graphite nanofilm (50 nm thick) / Si (20 nm thick) from Example 3; device sensitivity is 5.7 × 10⁻⁶ at -1V bias. 8 μCGy air -1 cm -2 The response speed is below 100ns (due to circuit design limitations, the maximum response speed test can only reach 100ns).

[0065] Detector II: Employs the graphite nanofilm (2nm thick) / Si (5nm thick) from Example 2; device sensitivity is 3.4 × 10⁻⁶ at -1V bias. 8 μCGy air -1 cm -2 The response speed is below 100ns (due to circuit design limitations, the maximum response speed test can only reach 100ns).

[0066] Detector III: Employs a low-orientation graphite nanofilm (2nm thick) / Si (5nm thick), with a device sensitivity of 2.3×10⁻⁶ at a bias voltage of -1V. 8 μCGy air -1 cm -2 The response speed is below 100 ns (limited by circuit design, the response speed limit test can only be measured up to 100 ns); the graphite nanofilm of detector III is prepared by solution evaporation (without centrifugation orientation) and has an orientation degree of 86%.

[0067] Detector IV: Response sensitivity of a classic single SnS nanosheet soft X-ray detector (1.55 × 10⁻⁶ at 1 V). 4 μCGy air -1 cm -2 and response speed (7ms);

[0068] Therefore, it can be concluded that the highly oriented graphite nanofilm / silicon semiconductor heterojunction prepared by this invention has significant advantages in both response sensitivity and device response speed. Devices prepared from highly oriented graphite nanofilms can have excellent applications in high-sensitivity, high-resolution, and fast X-ray imaging. Comparison shows that the hot electrons generated by the graphite nanofilm and Si stabilize the hot electrons within the nanofilm, and the strong Coulomb scattering of the graphite nanofilm can dramatically increase the number of hot electrons, thereby amplifying the photocurrent signal.

[0069] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for preparing a self-supporting graphite film, characterized in that, Includes the following steps: (1) The dispersion of graphene oxide is injected into a rotating centrifuge tube at one time, and an incompletely dried graphene oxide film is formed on the inner wall of the centrifuge tube. The solvent volume content is 10~40%. The centrifuge tube is made of filter membrane and arranged along the horizontal axis. The horizontally arranged centrifuge tube is supported by a rigid support tube. The support tube has a flow guiding structure to guide the solvent filtered by the filter membrane from the outer wall of the centrifuge tube. The solvent forms circumferential shear during centrifugation to orient the two-dimensional material. The flow guiding structure is a series of through holes evenly distributed on the wall of the support tube. (2) Immerse the filter membrane carrying the incompletely dried graphene oxide membrane in a highly volatile solvent to separate the graphene oxide membrane from the filter membrane. (3) Remove the graphene oxide film from the highly volatile solvent using a carrier, and after drying, the graphene oxide film and the carrier are separated to obtain the graphene oxide film. (4) The graphene oxide film is placed in air at 200-300 °C for 0.5-2 h, and then treated in a graphite furnace at 2500 °C or above for more than 2 hours under argon protection to obtain a self-supporting graphite film. The filter membrane is a hydrophilic polytetrafluoroethylene filter membrane; The average roughness of the hydrophilic polytetrafluoroethylene filter membrane is higher than 2 μm; The highly volatile solvent in step (3) includes one or more of isopropanol, ethanol, acetone, and ethyl acetate; The graphene oxide dispersion is formed by dissolving graphene oxide in a solvent and a graphitizable polymer. The graphitizable polymer and graphene oxide in the dispersion account for 0.05 wt% to 1 wt%; the mass ratio of graphitizable polymer to graphene oxide is 10:10 to 1:

10. The graphitizable polymers are polyacrylonitrile, lignin, or polyimide; The solvent is dimethylformamide, dimethylacetamide, or N-methylpyrrolidone.

2. The method according to claim 1, characterized in that, The centrifuge tube rotates at a speed of 500 r / min or higher, and its inner diameter is 20-100 cm.

3. A soft X-ray detector, characterized in that, The invention comprises a semiconductor substrate and a self-supporting graphite film prepared by the method of claim 1, which are heterogeneously integrated; the semiconductor substrate has a thickness of 2 nm to 20 nm and serves as the main X-ray photonic layer; the self-supporting graphite film has a thickness of 5 nm to 50 nm and serves as the secondary absorption layer and the main gain layer.

Citation Information

Patent Citations

  • Method for effectively preparing high-orientation and high-compactness two-dimensional material thin film

    CN108568926A

  • Preparation method of independent self-supporting artificial nano-graphite film

    CN111547716A

  • Ultrathin graphene suction filtration membrane and preparation method thereof

    CN117466291A